2016
DOI: 10.1155/2016/5302120
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Autologous Adipose Stem Cells in Patients with Multiple Sclerosis: Preliminary Results

Abstract: The clinical outcome of autologous adipose stem cell (ASC) treatment of patients with multiple sclerosis (MS) was investigated following one year of observation. Methods. The clinical and MRI outcomes of 16 ASC-treated patients with RRMS and SPMS are reported after a one-year follow-up period. Results. At 18 months of follow-up, some patients showed “enticing” improvements on some exploratory efficacy measures, although a significant benefit was not observed for any measure across the entire group. Neither the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…By this mechanism, ADSCs have not only been successful at treating diseases in animal models but also in humans. Recently, Stepien et al (2016) used ADSCs to treat Multiple Sclerosis in human; they showed that intrathecal treatment of ADSCs was a suitable therapy for cases with aggressive disease progression (Stepien et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…By this mechanism, ADSCs have not only been successful at treating diseases in animal models but also in humans. Recently, Stepien et al (2016) used ADSCs to treat Multiple Sclerosis in human; they showed that intrathecal treatment of ADSCs was a suitable therapy for cases with aggressive disease progression (Stepien et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…After 18 months of follow-up, ASCs were shown to be safe, but with no significant benefits having been reported. [58] Notably, there was no disease progression, and the authors noted that although this was an attractive strategy, the treatment should be reserved for patients with aggressive disease progression. In the second study, a blinded randomised trial, 26 patients were treated with either low-dose/high-dose ASCs or placebo.…”
Section: Researchmentioning
confidence: 99%
“…There is evidence supporting a role the antiinflammatory capacity of ADSCs for this devastating disorder [99][100][101], as well as their neuron-rebuilding capability. Indeed, both SVF and ADSCs appear to be effective in animal models of this disease [99,[102][103][104][105][106][107][108][109][110][111]. Bowles, et al, reported an advantage of SVF over ADSCs in the experimental autoimmune encephalomyelitis (EAE) model in the mouse [103,104].…”
Section: Msmentioning
confidence: 99%